Strategy for reducing rubber wear emissions: The prospect of using calcium lignosulfonate - Michaela Džuganová; Radek Stoček; Marek Pöschl; Ján Kruželák; Andrea Kvasničáková; Ján Hronkovič; Jozef Preťo (eXPRESS Polymer Letters, 2024)
This study explores the transformative potential of calcium lignosulfonate (CaL) as a sustainable additive in rubber composites based on nitrile rubber (NBR) and styrene-butadiene rubber (SBR). Through comprehensive mechanical testing, fatigue crack growth (FCG) analysis, and scanning electron microscopy (SEM), we evaluated the tensile strength, elongation at break, surface morphology, and crack growth behavior of these innovative composites. By incorporating CaL into carbon black-reinforced rubber compounds (RUB/CB) based on nitrile rubber and styrene-butadiene rubber, we achieved good dispersion of both components as well as satisfactory morphology, resulting in tensile strengths of 16.3 and 12.7 MPa, respectively. While the CB/CaL hybrid did not significantly influence the intrinsic strength of the rubber samples, the ultimate strength of these compounds increased drastically – over five-fold compared to RUB/CB – indicating great potential for real-life applications. This study underscores the promise of lignin-based additives in the development of eco-friendly, highperformance rubber materials.